Salt reduction and low-sodium salt substitutes: Awareness among health-care providers in Mangalore, Karnataka - K Afshaan Fathima; Madhavi Bhargava (Wolters Kluwer Medknow Publications, 2018)
Introduction: Hypertension is an important noncommunicable disease of global significance. Low-sodium salt substitutes (LSSS) are increasingly being used for hypertensive persons. The sodium content of these salts is reduced by substituting varying proportion of sodium with potassium. Materials and Methods: The present study was done to assess the awareness of ideal salt intake, knowledge of the availability of LSSS, their indications, and contraindications among 165 doctors of Mangalore, Dakshina Kannada. Results: The knowledge of correct upper limit of salt as 5 g/day was present in 46.7% of the participants and that for the availability of LSSS in 71%. Knowledge about the mechanism of sodium reduction with potassium substitution was found to be correct in 17.6% participants. LSSS were prescribed by 31 (18.8%), and 118 (71.5%) participants did not know about their contraindications in patients with renal disease, cardiac problems, and diabetes and patients on K-sparing diuretics and painkillers. Conclusions: The study underlines the importance of knowledge about salt reduction, LSSS, their indications, and contraindications in doctors. Regulated availability of these salts and widespread information for the primary care physicians to prevent mishaps following their use is recommended.